Equity in the hybrid office : in the post-pandemic workplace, leaders and employees alike must work to ensure the fair treatment of both in-person and remote workers - Odom, Curtis L.; Franczak, Jennifer; McAllister, Charn Patrick, 1983- (MIT Sloan Management Review, 2022)
When the pandemic shifted many people to remote work, long-held attitudes about the practice shifted as well. Now, as many organizations are adopting hybrid work arrangements, it's imperative that leaders end the tendency to overlook remote employees' contributions and aspirations. The authors offer recommendations for both leaders and employees to help them work toward equity and access for both in-person and remote personnel.